Històries escrites, històries cantades i històries pintades. Els goigs en el Barroc valencià. - GOMIS CORELL, JOAN- CARLES (Scripta, 2018)
From the beginning of the sixteenth century, the implantation of the printing press and the consequent affirmation of the written tradition caused that the goigs initiated, particularly in Valencia, a progressive diffusion process. The new invention facilitated the reproduction of the sacred image to which the composition was dedicated, so that, in addition to transmitting the text of the prayer, they achieved the value and function of devotional prints. They did not include, however, music, which would indicate that it had to be trusted to the memory and good performing of the singers of the musical chapels. The subsequent implantation of the counterreformist postulates favoured the dissemination and popularization of goigs, which culminated in the second half of the 18th century, when Baroque religiosity was questioned by the new illustrated postulates. The texts, from the praise and invitation to meditation typical of the 16th century, were mainly transformed into requests for favours and narrative stories of appearances, finding images and miraculous events, full of theatricality and effect. The counter-reform Church saw in goigs a good way to exalt sacred characters and stimulate the piety of the faithful without getting rid of the literary tradition of cult hagiographies. Goigs happened to be small versions of this literary genre, as well as of the "true stories", making them understandable to the faithful, thanks to the orality conferred by singing, written stories, which, at the same time, they served the painters to compose their painted stories.